2011
DOI: 10.1002/bdrb.20318
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of current developmental toxicity testing strategies: a case of babies and their bathwater

Abstract: This review is the second in a series of four papers emanating from a workshop entitled "Developmental Toxicology-New Directions," which was sponsored by the ILSI Health and Environmental Sciences Institute's (HESI) Developmental and Reproductive Toxicology Technical Committee. The present review analyzes the strengths and weaknesses of current developmental safety testing approaches in an effort to identify those strengths that should be retained in the future versus the weaknesses that should be eliminated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…However, while negative preclinical reproductive toxicology test results are reassuring, there is no assurance that negative results obtained by testing drugs in animals can definitively predict that a drug will lack teratogenic effects in humans . Similarly, it cannot be concluded that agents teratogenic in animals will necessarily produce teratogenic effects in humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, while negative preclinical reproductive toxicology test results are reassuring, there is no assurance that negative results obtained by testing drugs in animals can definitively predict that a drug will lack teratogenic effects in humans . Similarly, it cannot be concluded that agents teratogenic in animals will necessarily produce teratogenic effects in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Further progress in this area would be accelerated by regulatory steps that preclude the use of in vivo data unless they come from a formally validated model and therefore have a known predictivity (Carney et al, 2011). Uses of the zebrafish assay (Selderslaghs et al, 2011;Padilla et al, 2012;truong et al, 2014), the embryonic stem cell test (eSt) (van Dartel and Piersma, 2011;Seiler and Spielmann, 2011) and further developments on the basis of ReProtect test systems (Piersma, 2010) could immediately fill the gap until assays based on human cells become available.…”
Section: Fig 13: Schematic Explanation Of Quantitative In Vitro -In mentioning
confidence: 99%
“…The negative consequences of this practice include unnecessary animal use, cost, and effort as the irrelevant findings generated are further investigated. This testing scheme also can lead to the erroneous classification and labeling of compounds which pose little risk to humans'' (Carney et al, 2011). The second paper (Brannen et al, 2011) is a summary of the discussion of a workshop on developmental toxicology -new directions, held by ILSI and HESI.…”
Section: Pesticidementioning
confidence: 99%